Development of an Optimal Resupply Strategy for the Lunar Gateway in Near-Rectilinear Halo Orbit (2025)
Crewed space missions in recent years have aroused great interest from space agencies since maintaining a human presence in space opens the possibilities of exploring beyond what is known until now. However, guaranteeing this continuous permanence in space stations represents a significant challenge, especially in the development of this work, which proposes the resupply of a station beyond Earth's orbit. In this work, a resupply strategy is developed for the lunar Gateway station to achieve optimal and efficient planning. The study is divided into two main stages. The first consists of the logistical analysis of the crew's needs to maintain the proper development of their activities in space environment conditions, taking as reference three sources of information in order to generate a daily consumption estimate per crew member for each of the essential resources identified. The second focuses on the optimization of the total Delta V required during the transfer maneuvers, seeking to minimize the fuel mass and, in turn, achieving this reduction to lower the costs associated with each mission; this optimization was achieved using NASA's General Mission Analysis Tool (GMAT), allowing reliable results to be obtained. Subsequently, the integration of both stages makes it possible to generate an optimal and sustainable resupply plan. The results support the proposal of a sustainable and scalable resupply plan capable of adapting to the crew's consumption needs.